Analysis of the Effect of Frequency on Wavelength and Sound Size in Sound Generator Experiments - Firda, Rafirda Fitri Muawani; Nita Amelia; Riris Arisa; Syifa Ullayla; Yanto Yanto; Adam Malik (Sunan Kalijaga Journal of Physics, 2023)
Waves are one of the abstract physics materials in the world of physics and will be a separate problem in studying them. The wave superposition experiment was carried out using software using Vlab. The aim of this research is to analyze the effect of frequency changes on wave length and sound. The method used is to prepare tools and materials, namely PCs/laptops with frequencies of 100 Hz, 500 Hz, 1000 Hz, 1500 Hz and 2000 Hz. This is done for different audio frequencies as well. Then the results of the merger were opened with Audacity and then analyzed and compared with the initial wave. So that a superposition is produced that the effect of frequency on wavelength is inversely proportional, the greater the frequency issued, the smaller the resulting wavelength, while the effect of frequency on sound waves is